A new species of Platyseius Berlese (Acari: Mesostigmata: Blattisociidae) from Iran, and a key to the world species of the genus - Kazemi, Shahrooz; Payandeh, Majid; Saberi, Sepideh (Zootaxa, 2016)
We describe a new species of Platyseius Berlese, 1916 belonging to the subglaber species group, P. persicus sp. nov., on the basis of adult females collected in moist soil and litter in Kashmar, northeastern Iran and Nowshahr, northern Iran. A key to females of Platyseius is presented.